PENGARUH PROMOSI PENJUALAN TERHADAP REPURCHASE MELALUI TRIAL DENGAN MODERASI FEAR OF LOSING FACE PADA SOGO DEPARTMENT STORE SURABAYA - Indrianawati Usman; Rizky Adhitya Arnando (EKUITAS (Jurnal Ekonomi dan Keuangan), 2007)
This paper examines the influence of sales promotion related to trial which is moderated by fear of losing face and influence of trial related to repurchase in Sogo Department Store Surabaya. The variables used in this reseach are sales promotion (X), fear of losing face (Z1), trial (Z2), and repurchase (Y). The result indicates that the effect of sales promotion on trial is weak when fear of losing face is perceived.  In other words, perceived fear of losing face reduces customers’ sensitivity to the trial. The second result indicates that trial is related to repurchase.